Price Analysis of Systemic Therapies and Transarterial Radioembolization for Treatment of Unresectable Hepatocellular Carcinoma - Abimbola O. Williams; Nicholas Anderson; Young-Gwan Gwon; Wendy Wifler (Journal of Market Access & Health Policy, 2025)
Systemic therapy (ST) and transarterial radioembolization (TARE) are widely used treatments for advanced-stage hepatocellular carcinoma (HCC). This study quantified the significant variability in treatment costs for unresectable HCC from payer and provider perspectives. An Excel-based price analysis model was developed to estimate the prices of ST and TARE over a 21-month time horizon using 2015–2021 data. Median prices were calculated from Medicare Average Sales Price (ASP), provider Wholesale Acquisition Cost (WAC), and Average Wholesale Price (AWP). Sensitivity analyses evaluated price fluctuations associated with a ±10% variation in treatment duration. ST prices demonstrated marked variability across perspectives, with the median ASP at $175,625, WAC at $198,719, and AWP at $262,892. However, TARE prices were stable, ranging from $21,594 to $24,052. Sensitivity analyses revealed that treatment duration variation resulted in price changes of $35,000–$50,000 for ST, compared with ~$5000 for TARE. The variability in ST pricing was driven by treatment duration and drug-specific pricing mechanisms, particularly immunotherapy-based regimens, which accounted for the higher cost range. Conversely, TARE’s consistent pricing is attributed to standardized procedural costs. Substantial variability exists in ST prices compared with the consistent costs of TARE, underscoring the economic advantage of TARE in appropriate clinical contexts.